ИНДУЦИРОВАННЫЕ ПЛЮРИПОТЕНТНЫЕ СТВОЛОВЫЕ КЛЕТКИ В РЕГЕНЕРАТИВНОЙ МЕДИЦИНЕ, ФАРМАКОЛОГИИ И НАУКЕ О СТАРЕНИИ (Experimental biology, 2015)
The discovery of induced pluripotent stem cells in 2006 opened new capabilities for the use of stem cells in regenerative medicine, research of ageing mechanisms, pathogenesis of genetic disorders and clinical drugtrials. However, there are substantial drawbacks for the use of induced pluripotent stem cells in medicine and pharmacology. In this review we discussed advantages and limitations of this technology in regards toregenerative medicine, pathogenesis of genetic conditions and clinical drug trials.
Keywords: pluripotent stem cells; pathogenesis